APPLICATION OF FINGER PAINTING TECHNIQUES IN FINE ARTS LEARNING FOR GRADE IV STUDENTS OF STATE ELEMENTARY SCHOOL KEBONMANIS 01 CILACAP - Rahma, Restu Fadilla (Eduarts: Jurnal Pendidikan Seni, 2025)
This study aims to describe the application of finger painting techniques in fine arts learning for fourth-grade students of Kebonmanis 01 Cilacap Elementary School. The approach used is descriptive qualitative, with data collection techniques through observation, interviews, documentation, and analysis of students' artwork. The research findings show that the application of finger painting techniques provides a positive contribution to the development of aesthetic abilities, fine motor skills, and creative expression of students. The learning process is carried out in three main stages: project planning, project implementation, and project evaluation. Assessment is carried out using authentic assessment principles according to the Independent Curriculum, which focuses on students' understanding of the elements of art, courage in experimenting, and originality of ideas. The results of the study show that this method successfully encourages most students to show positive development. A total of 47% of students are in the Very Well Developed (BSB) category, 33% are Developing According to Expectations (BSH), and the rest are Starting to Develop (MB). Students are able to produce two-dimensional works of art that are not only visually attractive, but also reflect an understanding of themes, color composition, and courage in expression. These results show that the finger painting technique is an effective and fun alternative in improving the visual potential of students at the elementary school level.